Phase Angle and Its Determinants Among Adolescents: Influence of Body Composition and Physical Fitness Level - De Moraes-Ferrari, G (Nature Research, 2024)
To examine the association between levels of physical fitness, parameters of body composition and phase angle (PhA) amongst adolescents. A total of 152 adolescents (84 girls) aged 11–16 years were included in this study. Weight and height were measured and the body mass index (BMI) was calculated. Bioelectrical impedance analysis (BIA) provided resistance and reactance parameters to calculate fat-free mass (FFM), PhA and fat mass (%FM). The following physical fitness variables were analysed: flexibility, abdominal muscular endurance, upper and lower limb explosive strength, agility, speed and cardiorespiratory fitness. Generalized Linear Models were applied to verify differences across sexes. Stepwise linear regression was used to establish an association between the variables studied. The study established an association between PhA and weight, FFM, BMI, FM, %FM and medicine ball throw (MBT) for girls. As for the boys, an association was verified between PhA and weight, FFM, BMI, standing long jump (SLJ), MBT and the three allometric VO2peak variables analyzed. An association was found between PhA and the boys’ 4-m shuttle run test (4SRT) and 20-m sprint test (20SRT). Boys showed a greater phase angle than girls; In girls, BMI and %FM, were determinant of 32.4% (r = 0.57). PhA variability which is influenced by physical fitness, body composition and, therefore, the tissues electrical conductivity. Furthermore, boys’ height, FFM, upper limb strength, and agility account for 58.4% (r = 0.76) PhA variability. There was a positive correlation between the physical fitness tests and the PhA. © The Author(s) 2024.